Prevalence of endothelial nitric oxide synthase E298D polymorphism in Turkish patients with essential hypertension - KAYHAN, FİGEN ESİN (My University, 2013)
Aims: Our aim was to evaluate the effects of endothelial nitric oxide synthase (eNOS) E298D polymorphism in obesity variables and essential hypertension (eHT) development risk. The genotype frequencies of E298D polymorphism in eHT patients and non-hypertensive (non-HT) controls (proven to have normal coronaries angiographically) were analyzed for their association with demographic and obesity related data of the eHT patients and controls. Materials and methods: eNOS gene E298D genotypes were determined with qPCR. Results: The eNOS E298D polymorphism frequencies for 298E/E, 298E/D and 298D/D genotypes were respectively as 41.1%, 44.6%, 14.3% in subjects eHT and 52.8%, 38.9%, 8.3% in the non-HT groups. The combined E298D homozygous polymorphic and heterozygous genotypes were found to have a decreasing effect on serum total-cholesterol levels in comparison to wild-type genotypes in eHT patients but not controls. Conclusions: Our results support the idea that, the eNOS E298D polymorphism, which is not associated with hypertension, may increase the risk of hypertension when associated with high serum total-cholesterol levels. © 2013 Diabetes India. Published by Elsevier Ltd. All rights reserved.
Keywords: E298D polymorphism; eNOS; Fat mass; Lipid; Obesity